Evaluation of Medical Sciences Students’ Perception, Barriers, and Attitude toward Scientific Research: A Cross-sectional Study in Makkah Region, Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: Medical research skills at the undergraduate level is increasingly discussed as having a potential role indeveloping certain skills in students including decision making, problem-solving, and critical thinking. Therefore,this study aimed to evaluate the perception, barriers, and attitude of medical sciences students toward scientificresearch in Makkah region of Saudi Arabia. Methods: The data collected between August and September 2019using an electronic questionnaire that was distributed to medical sciences students at Makkah region including(4th, 5th, 6th years, and interns). Results: Total number of participants who answered the questionnaire was 411health-care students. Most of the students were females (70.6%), only 29.4% of them were male students. Mostof them (72.8%) agreed that scientific research is essential for undergraduate students and about 73.2% of themsaid that they will participate in any available research opportunity. About 70.3% of the respondents reported thatthey do not know whom to contact if they want to conduct research and about 61.6% of the respondents reportedthere were few opportunities to do research in their college. Conclusion: Although students have good attitudeand good perception toward research, there are some barriers that should be overcome to encourage studentparticipation in research activities in Makkah region’s universities of Saudi Arabia.